Зубы судьбы: сибирский детектив: повести : рассказы / Александр Бушков, Владимир Величко - Бушков Александр Александрович (ОЛМА Медиа Групп, 2015)
Экземпляры: ф.7 (20160919) / Инвентарный номер: 41604 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4